Подвиги Гостомысла. Славянский дед Рюрика: [роман] / Василий Седугин - Седугин Василий Иванович (Иду на Вы!, 2012)
Экземпляры: ф.6 (20230407) / Инвентарный номер: 3924 И / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: С 28 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44